2009
DOI: 10.1080/03639040802660489
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multicomponent crystal formed between indomethacin and lidocaine

Abstract: The complexation process was estimated to be as follows: (i) mixing and contact of two components, (ii) disorder of crystalline LDC by grinding or fusion, and then (iii) crystal growth by heating. In addition, 1H-NMR coupled with microchanneled cell for synthesis monitoring revealed that a primary interactive force between IDM and LDC molecule was coulomb energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…25,26 Notably, two drug−drug cocrystals involving IND are already known, namely, IND−carbamazepine 27 and IND− lidocaine. 28 CAFF was chosen as a coformer because it can be found together with IND, owing to their synergic effects, 29 in Difmetre, a pharmaceutical containing IND, CAFF, and prochlorperazine dimaleate in a molar ratio 1:5.6:0.07. Difmetreć an be administered as a film-coated or effervescent tablet or as a suppository and is currently used to treat strong migraines, especially hypnic headaches.…”
Section: ■ Introductionmentioning
confidence: 99%
“…25,26 Notably, two drug−drug cocrystals involving IND are already known, namely, IND−carbamazepine 27 and IND− lidocaine. 28 CAFF was chosen as a coformer because it can be found together with IND, owing to their synergic effects, 29 in Difmetre, a pharmaceutical containing IND, CAFF, and prochlorperazine dimaleate in a molar ratio 1:5.6:0.07. Difmetreć an be administered as a film-coated or effervescent tablet or as a suppository and is currently used to treat strong migraines, especially hypnic headaches.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8 The formation of salts or solvates of APIs is a typical approach to circumvent the problem of low solubility. [9][10][11] In this context, cocrystals of a given API have gained considerable interest in recent years. Cocrystals are crystalline phases with two or more components consisting of uncharged organic compounds, which interact via intermolecular forces.…”
Section: Introductionmentioning
confidence: 99%
“…A mathematical model, based on cocrystal dissociation and ionization solution equilibria was also developed to describe the pH solubility profile for a zwitterionic drug substance and an acidic coformer. Lidocaine Indomethacin was obtained from ethanol, and characterized by the standard sequence of solid-state analytical techniques [43]. The same cocrystal product was obtained using solvent-less grinding and heating, which suggested that the formation process consisted of the steps of achieving an intimate mixture of the ingredients, inducing disorder in the solids by grinding or fusion, and achieving crystal growth by heating.…”
Section: Fifteen Cocrystals Of N-[4-({6-[4-(trifluoromethyl)phenyl]pymentioning
confidence: 99%